2013
DOI: 10.1016/j.ridd.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Using developmental trajectories to examine verbal and visuospatial short-term memory development in children and adolescents with Williams and Down syndromes

Abstract: Ronnberg, J. (2013). Using developmental trajectories to examine verbal and visuospatial short-term memory development in children and adolescents with Williams and Down syndromes. Research in Developmental Disabilities, 34(10), pp. 3421-3432. doi: 10.1016/j.ridd.2013.07.012 This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
1
29
2
1
Order By: Relevance
“…Smith and Jarrold (2014) [32] also demonstrated deviant verbal performance on short-term memory recall in people with DS. Carney et al (2013) [33] confirmed the poor verbal short-term memory of people with DS in contrast to the poor visuospatial short-term memory of people with WS from developmental between-group comparisons, suggesting a clear double dissociation of verbal and visuospatial short-term memory systems in these two syndromes. Their finding is compatible with our results that people with DS have poor verbal ability.…”
Section: Discussionmentioning
confidence: 68%
“…Smith and Jarrold (2014) [32] also demonstrated deviant verbal performance on short-term memory recall in people with DS. Carney et al (2013) [33] confirmed the poor verbal short-term memory of people with DS in contrast to the poor visuospatial short-term memory of people with WS from developmental between-group comparisons, suggesting a clear double dissociation of verbal and visuospatial short-term memory systems in these two syndromes. Their finding is compatible with our results that people with DS have poor verbal ability.…”
Section: Discussionmentioning
confidence: 68%
“…In terms of STM, individuals with WS tend to show a relative strength in verbal STM and a relative weakness in visual-spatial STM and other visuospatial skills (e.g. Carney et al, 2013;Klein & Mervis, 1999;Menghini, Addona, Costanzo, & Vicari, 2010;O'Hearn, Courtney, Street, & Landau, 2009;Vicari, Bellucci, & Carlesimo, 2003;Wang & Bellugi, 1993; but see Jarrold, Phillips, & Baddeley, 2007), a pattern that matches their uneven cognitive profile. Some researchers have argued that the impression of superior linguistic skills in those with WS is an artefact of hypersociability combined with superior verbal memory (Gosch, Stading, & Pankau, 1994;Thomas et al, 2010;Udwin & Yule, 1991).…”
Section: Developmental Delays In Phonological Recodingmentioning
confidence: 99%
“…Individuals with DS display broad weaknesses in language, including expressive vocabulary and grammar (Naess, Lyster, Hulme, & Melby-Lervåg, 2011), and phonological awareness (Naess, Melby-Lervåg, Hulme, & Lyster, 2012;Roch & Jarrold, 2008), although receptive vocabulary appears to be in line with non-verbal mental age (Laws & Bishop, 2004;Naess et al, 2011). In terms of short-term memory (STM), individuals with DS usually show relative weaknesses in verbal STM (see a range of studies including: Carney, Henry, Messer, Brown, Danielsson, & Rönnberg, 2013;Jarrold & Baddeley, 1997;Laws & Bishop, 2003;Smith & Jarrold, 2014b; Developmental delays in phonological recoding Vicari, Marotta & Carlesimo, 2004;, combined with relative strengths in visuospatial STM (e.g., Carretti & Lanfranchi, 2010;Yang, Conners, & Merrill, 2014). Importantly, these relative strengths in visuospatial STM occur in comparison to verbal STM, not in comparisons to mental age, as some visuospatial abilities are mental age appropriate and others are slightly below mental age expectations (Yang et al, 2014).…”
mentioning
confidence: 99%
“…The language development of children with Down syndrome (DS) is continuous, there is slowness in the beginning of acquisition and a differentiated rhythm of development, though [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%